Establishing and prioritizing research questions for the prevention, diagnosis and treatment of hair loss (excluding alopecia areata): the Hair Loss Priority Setting Partnership. (1st February 2018) - Macbeth, A.; Tomlinson, J.; Messenger, A.; Moore‐Millar, K.; Michaelides, C.; Shipman, A.; Kassim, J.; Brockley, J.; Szczecinska, W.; Farrant, P.; Robinson, R.; Rodgers, J.; et al.
Summary: Hair and scalp problems are common. Various conditions can result in hair loss and may present as increased hair shedding, hair thinning or patchy to complete hair loss. In some conditions the hair may regrow, in others the alopecia (hair loss) is permanent. Frequently overlooked is the psychological impact of hair loss on an individual. The visible nature of hair loss and fear of progression may lead to low self‐esteem, anxiety and depression. Unfortunately, there is a lot of uncertainty around the most effective treatments for these disorders. This study, funded by the charity Alopecia UK, aimed to identify uncertainties in hair loss management, prevention, diagnosis and treatment that are important both to people with hair loss and to healthcare professionals. This was done by creating a hair loss 'priority setting partnership' (PSP) between patients, their carers and relatives, and healthcare professionals, to identify the most important uncertainties in hair loss. This study presents the top 10 research priorities for hair loss (excluding alopecia areata) to guide researchers and funding bodies to support studies important both to patients and clinicians.